PENGEMBANGAN BAHAN AJAR BAHASA ACEH UNTUK SISWA KELAS IV SEKOLAH DASAR DI NANGGROE ACEH DARUSSALAM - Ramli - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2009)
The objective of this research is to develop the learning materials which are integrated of language skills: listening, speaking, reading, and writing, and the component of vocabulary and language structure. This research was carried out at the fourth year of the elementary school, ‘Sekolah Dasar Negeri 1’ Banda Aceh and ‘Sekolah Dasar Muhammadiyah 1’ Banda Aceh, Nanggroe Aceh Darussalam in September 2003 and from July to December 2007. Research methodology used is the research and development (RD) by Dick and Carey. Instruments used to collect data were questionnaire, interview, and test. Then, the data analyzed qualitatively and quantitatively. The findings of the research are two units of learning materials which is each of it consist of four topics of materials. This research concludes that the product of the development of learning materials of Acehnese language is effective to be applied in elementry school.